Psychosocial Twin Cohort Studies in Japan: The Keio Twin Research Center (KoTReC). (15th December 2019) - Ando, Juko; Fujisawa, Keiko K.; Hiraishi, Kai; Shikishima, Chizuru; Kawamoto, Tetsuya; Nozaki, Mari; Yamagata, Shinji; Takahashi, Yusuke; Suzuki, Kunitake; Someya, Yoshiaki; Ozaki, Koken; Deno, Minako; et al.
Abstract: The Keio Twin Research Center (KoTReC) was established in 2009 at Keio University to combine two longitudinal cohort projects — the Keio Twin Study (KTS) for adolescence and adulthood and the Tokyo Twin Cohort Project (ToTCoP) for infancy and childhood. KoTReC also conducted a two-time panel study of self-control and psychopathology in twin adolescence in 2012 and 2013 and three independent anonymous cross-sectional twin surveys (ToTcross) before 2012 — the ToTCross, the Junior and Senior High School Survey and the High School Survey. This article introduces the recent research designs of KoTReC and its publications.